Study and Analysis of the Coupling Between Regional Innovation Ability and Economic High Quality in Anhui Province - Wang, Gege; Deng, Xiaojie; Lin, Hanyu (International Journal of Global Economics and Management, 2024)
This study in Anhui province from 2003-2022, a total of 20 years of regional innovation and economic development of high quality data, through the regional innovation driven ability of measurement, high quality development level, regional innovation efficiency and the correlation of the three aspects, analyze the development of economic quality, based on regional innovation efficiency and high quality economic development data, establish coupling coordination model, empirical research on the coupling relationship between the two. Found in Anhui province in recent years on the economic quality level and scientific and technological innovation ability have been steadily improved, high quality economic development comprehensive level and regional innovation efficiency is obvious coupling effect, present good development trend, however, the level of science and technology and the imbalance between innovation environment optimization, at the same time the growth of economic benefits and economic efficiency between also there is a certain lag. How to make good use of the coupling relationship between the development of regional innovation ability and high-quality economic development in Anhui Province to realize the mutual promotion of development is the top priority. In order to further improve the level of high-quality economic development, this paper finally puts forward relevant countermeasures and suggestions according to the research results.